Interleukin‐25 and eosinophils progenitor cell mobilization in allergic asthma. Issue 1 (13th February 2018) - Tang, Wei; Smith, Steven G.; Du, Wei; Gugilla, Akash; Du, Juan; Oliveria, John Paul; Howie, Karen; Salter, Brittany M.; Gauvreau, Gail M.; O'Byrne, Paul M.; Sehmi, Roma
Abstract: Background: Eosinophil‐lineage committed progenitor cells (EoP) migrate from the bone marrow and differentiate locally to provide an ongoing source of mature eosinophils in asthmatic inflammatory responses in the airways. Sputum levels of EoP are increased in asthmatics compared to normal controls suggesting an exaggerated eosinophilopoietic environment in the airways. Understanding what factors promote EoP traffic to the airways is important to understand the diathesis of asthma pathology. Interleukin (IL)‐25, is an epithelial‐derived cytokine that promotes type 2 inflammatory responses. We have previously shown that levels of IL‐25 and expression of the IL‐25 receptor (IL‐17RA and IL‐17RB) on mature eosinophils are greater in allergic asthmatics compared to atopic non‐asthmatics and non‐atopic normal controls. In addition, these levels were increased significantly increased following allergen inhalation challenge and physiologically relevant levels of IL‐25 stimulated eosinophil degranulation, intracellular IL‐5 and IL‐13 expression and primed migration to eotaxin. The current study, examined the role of IL‐25 on allergen‐induced trafficking of EoP in atopic asthmatics. Methods: Asthmatics (n = 14) who developed allergen‐induced early and late responses were enrolled in the study. Blood was collected at pre‐ and 24 h post‐challenge. At each time point, surface expression of IL‐17RA and IL‐17RB on EoP was evaluated by flow cytometry. Migration assays examined the effect of IL‐25 on EoP chemotactic responses, in vitro. In addition, IL‐25 knockout ovalbumin (OVA) sensitized and challenged mice were studied to evaluate in vivo mobilization effects of IL‐25 on newly formed EoP and mature eosinophils. Results: There was a significant increase in numbers of blood EoP expressing IL‐17RB, 24 h post‐allergen inhalation challenge in allergic asthmatics. Pre‐exposure to IL‐25 primed the migrational responsiveness of EoP to stromal cell‐derived factor 1α. In OVA‐sensitized mice, knocking out IL‐25 significantly alleviated OVA‐induced eosinophil infiltration in the airway and newly formed eosinophils were reduced in the lung. Conclusions: The findings of this study indicate a potential role for IL‐25 in allergen‐induced trafficking of EoP to the airways and local differentiation promoting tissue eosiniophilia in asthmatic responses.